The complete mitogenome of Sokolov’s Dwarf Hamster (Cricetulus sokolovi) and implication of phylogenetic status - Qin, Boxin (Mitochondrial DNA B Resour, 2021)
There is still an obvious lack of information on Sokolov's Dwarf Hamster (Cricetulus sokolovi) which belongs to subfamily Cricetinae because the species is only rarely found in Gobi desert. In this study, we obtained the complete mitochondrial genome sequences of C. sokolovi. The genome is 16,292bp in length and has a base composition of 33.5% A, 30.5% T, 22.9% C, and 13.1% G. The mitogenome structure, consisting of 13 protein-coding genes, two rRNA genes (12S rRNA and 16S rRNA), 22 tRNA genes, and one control region, is similar to that of typical vertebrate mitochondrial genomes of other rodents. We restructured a Bayesian phylogenetic tree by using 12 species belonging to subfamily Cricetinae. As indicated by the phylogenetic tree, genus Cricetulus is polyphyletic group, and C. Sokolovi is the closest relative of Cricetulus griseus. The mitochondrial genome can provide basic data for further study on the phylogenetic relationship of subfamily Cricetinae.